2015
DOI: 10.1038/srep10969
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the association of Escherichia coli with diverse macroalgae in the lagoon of Venice

Abstract: Recent studies provided evidence that the macroalga Cladopohora in lakes hosts associated Escherichia coli, with consequences on the environmental and human health. We expanded these investigations to other macroalgae (Ulva spp., Sargassum muticum and Undaria pinnatifida) widespread in the lagoon of Venice (Italy). Attached E. coli were abundant, accounting up to 3,250 CFU gram−1 of alga. Macroalgal-associated isolates belonged to all E. coli phylogroups, including pathogenic ones, and to Escherichia cryptic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 66 publications
1
19
0
Order By: Relevance
“…This hypothesis suggests that different grass species morphology and zones in the VFS influenced successful sustainable survival and multiplication of E. coli population. This hypothesis supports some of the most important processes, which have been reported to have a significant influence on the successful survival and multiplication of E. coli not only in vegetation litters micro-biome, but also in other ecosystems, which include: (1) E. coli strains establishing encoding regulation mechanisms, such as the attaching and effacing regulators in pathogenic and commensals E. coli strains and E. coli’s quorum-sensing mechanism, which transforms it to initiate intercellular communication, and which allows the unicellular organism to behave like multicellular organisms (Kaper et al 2004); (2) E. coli’s multistep scheme nature of pathogenesis in occupying the new niche using adhesion and colonization morphological structures such as fimbriae (pili) and/or flagellin to attach to mucosal site; evade host defenses, multiply and damage the host cells (Kaper et al 2004); (3) E. coli’s ability to establish high metabolic niche and to utilize available dissolved organic carbon and other nutrients more efficiently than other existing resident microbial species that enables it to compete better than other resident microbes (Sweeney et al 1996) in the root system and to establish itself in the new environment and (4) finally, enhanced biofilm formation in the lentic water film in the plants litters (Quero et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis suggests that different grass species morphology and zones in the VFS influenced successful sustainable survival and multiplication of E. coli population. This hypothesis supports some of the most important processes, which have been reported to have a significant influence on the successful survival and multiplication of E. coli not only in vegetation litters micro-biome, but also in other ecosystems, which include: (1) E. coli strains establishing encoding regulation mechanisms, such as the attaching and effacing regulators in pathogenic and commensals E. coli strains and E. coli’s quorum-sensing mechanism, which transforms it to initiate intercellular communication, and which allows the unicellular organism to behave like multicellular organisms (Kaper et al 2004); (2) E. coli’s multistep scheme nature of pathogenesis in occupying the new niche using adhesion and colonization morphological structures such as fimbriae (pili) and/or flagellin to attach to mucosal site; evade host defenses, multiply and damage the host cells (Kaper et al 2004); (3) E. coli’s ability to establish high metabolic niche and to utilize available dissolved organic carbon and other nutrients more efficiently than other existing resident microbial species that enables it to compete better than other resident microbes (Sweeney et al 1996) in the root system and to establish itself in the new environment and (4) finally, enhanced biofilm formation in the lentic water film in the plants litters (Quero et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Interaction of VFS, infiltration into soil matrix, partitioning, biofilm formation, adsorption/detachment, straining and biological die-off/regrowth have to be combined to design and assess manure management strategies in association with projected overland flow regimes and pathogen loads (Blount 2015; Gallagher et al 2013; Pachepsky et al 2006; Quero et al 2015). While initial studies of manure-borne fecal microorganisms pathogens such as E. coil , developed in the 1980s, were typically concerned with pedon and hill slope scales, in recent years, hill slope and watershed scales have led insight into the effects of soil, vegetation, management, and weather on the fate and transport of fecal pathogens (Overcash et al 1981; Moore et al 1982, 1983, 1988; Guber et al 2005a, b, 2006, 2007; Pachepsky et al 2006; Moreira et al 2006; Allaire et al 2015; Rippy 2015).…”
Section: Pathogen Movement In Overland Flowmentioning
confidence: 99%
“…The biofilm formation by E. coil strains in environmental studies have indicated adaptation to secondary habitats outside their primary hosts including vegetation such as macroalgae and vegetative filter strips (Byappanahalli et al 2003; Moreira et al 2006; Quero et al 2015). Since pathogenic strains of E. coil utilize attaching and effacing histopathology induced through selective expression of virulence genes for Enteropathogenic E. coil (EPEC) and Enterohaemorrhagic E. coil (EHEC) that are expressed during biofilm formation (Kaper 2005; Kaper et al 2004) and could play a role in biofilm development in removal from overland flow (Kaper et al 2004; Moreira et al 2006).…”
Section: Improving Modeling Of Fate and Transport Of Fecal Organismmentioning
confidence: 99%
“…The main aim of the experiment was to test whether communities that were stressed by a few days of exposure to tetracycline in low and intermediate doses were less resilient after the pulse disturbance of the community by the addition of three allochthonous bacterial strains, as previously suggested (Corno et al, ). E. coli was not able to permanently establish in either control or antibiotic‐disturbed communities, despite the three invading strains had been isolated from aquatic environments and were able to grow in lake water medium (Quero et al, ). After a slight increment for the first 24 hr after their addition, E. coli abundance declined in all the vessels to reach numbers below 2% at day 27.…”
Section: Discussionmentioning
confidence: 99%
“…In order to increment the survival chances of the inoculated allochthonous E. coli within the indigenous microbial communities already established in the chemostat vessels, three strains were selected to compose the inoculum. The E. coli strains that were previously isolated from water and floating macrophytes in the Venetian Lagoon (Perini, Quero, García, & Luna, ; Quero et al, ) were thus selected based on their ability to grow in freshwater medium (either the autoclaved lake water used in the experiment or the enriched artificial medium used for the preculturing) and their sensitivity to TET (Supporting Information Data ). From twelve tested strains, we selected three strains m‐FC‐5, m‐FC‐25 and m‐FC‐19 belonged to three phylogroups (A, B1 and B2, respectively) which grew well in the low carbon medium (Supporting Information Figure ).…”
Section: Methodsmentioning
confidence: 99%